2016
DOI: 10.3389/feart.2015.00089
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Soil Aggregation Following Phosphorus Additions in a Tropical Premontane Forest are Not Driven by Root and Arbuscular Mycorrhizal Fungal Abundances

Abstract: Tropical ecosystems have an important role in global change scenarios, in part because they serve as a large terrestrial carbon pool. Carbon protection is mediated by soil aggregation processes, whereby biotic and abiotic factors influence the formation and stability of aggregates. Nutrient additions may affect soil structure indirectly by simultaneous shifts in biotic factors, mainly roots, and fungal hyphae, but also via impacts on abiotic soil properties. Here, we tested the hypothesis that soil aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 97 publications
1
5
0
1
Order By: Relevance
“…Set in relation to the large‐scale field nutrient manipulation experiment conducted at these sites, the novel experimental approach contributes to distinguish among responses caused by primary microbial/fungal nutrient limitations versus secondary consequences of shifts in other ecosystem processes. Soil hyphal extractions from the field experiment similarly revealed increasing abundance following P (NaH 2 PO 4 ) additions at the 1,000‐m site (Camenzind, Papathanasiou et al., ), whereas, as reported here at 2,000 m, P caused no significant effects (unpublished data). Hamer et al.…”
Section: Discussionsupporting
confidence: 70%
“…Set in relation to the large‐scale field nutrient manipulation experiment conducted at these sites, the novel experimental approach contributes to distinguish among responses caused by primary microbial/fungal nutrient limitations versus secondary consequences of shifts in other ecosystem processes. Soil hyphal extractions from the field experiment similarly revealed increasing abundance following P (NaH 2 PO 4 ) additions at the 1,000‐m site (Camenzind, Papathanasiou et al., ), whereas, as reported here at 2,000 m, P caused no significant effects (unpublished data). Hamer et al.…”
Section: Discussionsupporting
confidence: 70%
“…Ghosh et al (2018) reported that 120:26 kg N/P application showed 12% higher macroaggregates than plots receiving only 120 kg N in 0 to15 cm, however microaggregates and silt-and-clay-sized fraction did not differ significantly. Camenzind et al (2016) observed 4.1% increase in water stable aggregates with P application rate of 10 kg ha −1 yr −1 than control in tropical ecosystem. Soil aggregation tends to increase SOC by influencing soil fertility and crop productivity by reducing erosion and controlling air permeability, water infiltration, and nutrient cycling (Singh et al, 2019b;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…Camenzind et al. (2016) observed 4.1% increase in water stable aggregates with P application rate of 10 kg ha −1 yr −1 than control in tropical ecosystem. Soil aggregation tends to increase SOC by influencing soil fertility and crop productivity by reducing erosion and controlling air permeability, water infiltration, and nutrient cycling (Singh et al., 2019b; Zhang et al., 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Mycelial productivity was significantly positively related to soil inorganic P (Figure 6), although mycelial biomass has previously been shown to be greater in more P-deficient forests (Potila et al, 2009). However, in some cases the proliferation of mycorrhizal hyphae into nutrient 'hotspots' has been observed both in laboratory experiments and natural systems (Ekblad et al, 2013), whilst the role of inorganic P in controlling rates of mycelial production has been demonstrated in forests using hyphal in-growth bags augmented with mineral P, and field manipulations using fertilizer applications (Hagerberg et al, 2003;Potila et al, 2009;Ekblad et al, 2013;Camenzind et al, 2016). In the current study, the tenuous nature of this relationship (being mainly driven by one sampling point in SL; Figure 6) limits interpretation of underlying mechanisms, and should be approached with caution.…”
Section: Discussionmentioning
confidence: 93%